An 11-point time course midgut transcriptome across 72 h after bloodfeeding provides detailed temporal resolution of transcript expression in the arbovirus vector, Aedes aegypti - Tsujimoto, Hitoshi; Adelman, Zach N. (Genome Research, 2023)
As the major vector for dengue, Zika, yellow fever, and chikungunya viruses, the mosquito Aedes aegypti is one of the most important insects in public health. These viruses are transmitted by bloodfeeding, which is also necessary for the reproduction of the mosquito. Thus, the midgut plays an essential role in mosquito physiology as the center for bloodmeal digestion and as an organ that serves as the first line of defense against viruses. Despite its importance, transcriptomic dynamics with fine temporal resolution across the entire digestion cycle have not yet been reported. To fill this gap, we conducted a transcriptomic analysis of A. aegypti female midguts across a 72-h bloodmeal digestion cycle for 11 time points, with a particular focus on the first 24 h. PCA analysis confirmed that 72 h is indeed a complete digestion cycle. Cluster and GO enrichment analysis showed the orchestrated modulation of thousands of genes to accomplish the midgut's role as the center for digestion, as well as nutrient transport with a clear progression with sequential emphasis on transcription, translation, energy production, nutrient metabolism, transport, and finally, autophagy by 24–36 h. We further determined that many serine proteases are robustly expressed as if to prepare for unexpected physiological challenges. This study provides a powerful resource for the analysis of genomic features that coordinate the rapid and complex transcriptional program induced by mosquito bloodfeeding.